USING A DISTRIBUTED VIRTUAL MEMORY SYSTEM TO MANAGE A SMART HOME - Байғараева, Жанель; Vyazigin, Stepan; Mansurova, Madina (Вестник ВКТУ им. Д. Серикбаева, 2023)
To solve the problem of fault tolerance, increase the convenience and security of the Smart Home hardware and software complex, the authors proposed using a simplified version of the SVM (Shared Virtual Memory) system in the form of a cluster with parallel data processing on various nodes of the system. This paper provides an example of creating an SVM system based on industrially manufactured Raspberry Pi 4 model B devices and a LAN and Wi-Fi switching network, and also presents the results of testing the fault tolerance of the resulting system. This paper provides an analysis of system performance, and a solution is proposed to improve performance by adding a new type of cache.